The Essential Contexts of Educational Law - González Alonso, Fernando (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2022)
This article sustains that Education Law is developed in different contexts. Hence the main purpose is to know and explicit the main contexts in which Education Law is developed in order to favour its knowledge, analysis and application. The main contexts are the following: the educational and competence one, the projection and social context, the ecclesial context, and the international andintercultural context. In addition, the investigative and analytical context, the axiological one and the planner and strategic one are also emphasised. In all of them, Educational Law assumes its leading role to bring values, attitudes and norms closer to the people and organisations as they need it, including the most needy and vulnerable communities. It is intended that the clarification of the contexts, their elements and characteristics, pave the way for the teaching of Education Law. Moreover, the teaching of Education Law may favour the knowledge of rights, norms, as well as the experience of values, so that society is more fair, peaceful and supportive.